Reflexiones en torno a la sostenibilidad de la dehesa - Pérez Díaz, A. (Geographicalia, 2016)
In the last century room the Spanish dehesa have wakened up a scientific interest that he only finds paragon and justification in the growing concern of the public opinion for the conservation and restoration of the environnient. In little time, the meadow has passed of being the paradigrn of the 'latifundismo" in its most pejorative conception, to becorne an unquestionahle model of sustainable development. Without denying this new conception a priori; this article tries to offer the keys for a reflection on the last sostenibilidad, present and future of the meadow. And he seeks to make it from a geographical, integrative perspective, far from fleeting fashions and stereotyped opinions.
Keywords: Dehesa; economy; s~istainability; l and-use systems